2013
DOI: 10.1111/ajop.12045
|View full text |Cite
|
Sign up to set email alerts
|

Cultural aspects within caregiver interactions of ultra‐Orthodox Jewish women and their family members with mental illness.

Abstract: The role of cultural dynamics and norms within families of persons with mental illness has been an underexplored subject, although the familial context has been recognized as influential. This subject was studied with 24 ultra-Orthodox Jewish mothers of persons with mental illness who live in a relatively closed religious community. While participating in the Keshet educational program designed for family caregivers in mental health, they wrote Meaningful Interactional Life Episodes that involved a dialogue ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…Creating partnership and collaboration within Keshet were special changes and adaptations that were made in the course. Weiss et al ( 29 ) describe the changes that were made to ensure compatibility for a specific population which required cultural adaptation, namely the ultra-orthodox Jewish community in Israel ( 26 ). This community is characterized by being secluded and viewing of modernity as a threat to religious beliefs.…”
Section: Resultsmentioning
confidence: 99%
“…Creating partnership and collaboration within Keshet were special changes and adaptations that were made in the course. Weiss et al ( 29 ) describe the changes that were made to ensure compatibility for a specific population which required cultural adaptation, namely the ultra-orthodox Jewish community in Israel ( 26 ). This community is characterized by being secluded and viewing of modernity as a threat to religious beliefs.…”
Section: Resultsmentioning
confidence: 99%
“…Our study stressed the emotional aspect of burden in a unique way. While other studies suggested that psychological burden is mainly manifested in self-centered expressions (.e.g., 'me' in the process), our participants, as members of a traditional collectivistic society (Weiss, Shor, & HadasÀLidor, 2013), experienced their emotional burden by reporting on their main subject of concern to their significant other À the aging parent's care. In other words, their prayers were directed towards the welfare of others.…”
Section: Discussionmentioning
confidence: 99%
“…Social growth was found to be stunted in this population due to stigma and lack of social support, therefore impacting on both social and occupational identity (Acero et al, 2017;Marimbe et al, 2016;Weiss et al, 2013).…”
Section: Occupations Offer Productivitymentioning
confidence: 97%